Human Brain Organoids to Decode Mechanisms of Microcephaly - Gabriel, Elke; Ramani, Anand; Altinisik, Nazlican; Gopalakrishnan, Jay (Frontiers in Cellular Neuroscience, 2020)
Brain organoids are stem cell-based self-assembling 3D structures that recapitulate early events of human brain development. Recent improvements with patient-specific 3D brain organoids have begun to elucidate unprecedented details of the defective mechanisms that cause neurodevelopmental disorders of congenital and acquired microcephaly. In particular, brain organoids derived from primary microcephaly patients have uncovered mechanisms that deregulate neural stem cell proliferation, maintenance, and differentiation. Not only did brain organoids reveal unknown aspects of neurogenesis but also have illuminated surprising roles of cellular structures of centrosomes and primary cilia in regulating neurogenesis during brain development. Here, we discuss how brain organoids have contributed to demystifying the complexities of microcephaly, which are unlikely to be identified in the existing non-human models. Finally, we discuss the yet unresolved questions and challenges that can be addressed with the use of brain organoids as in vitro models of neurodevelopmental disorders.